146k views
2 votes
Solve the system: 14x - 8y = -4 and 7x + 3y = 26 *

User Nikia
by
5.4k points

1 Answer

3 votes

Answer:

The solution is (2, 4)

Explanation:

Note that if we multiply the second equation by -2, the first term of this revised equation will be -14x, which will cancel out the +14x in the first equation:

14x - 8y = -4 => 14x - 8y = -4

-2(7x + 3y = 26) => -14x - 6y = -52

----------------------

-14y = -56, or y = 4

Substituting 4 for y in the first equation, we get 14x - 8(4) = -4, or

14x = 28 => x = 2

The solution is (2, 4)

User Keela
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.